Communities Vulnerability Mapping of Spermonde Coral Islands - Idrus, Rijal M.; Badawing, Dewi Y. Satari; Irwanto, I. Irwanto (Hasanuddin University, 2021)
The purpose of this research is to map the vulnerability of communities in seven islands of Spermonde. Vulnerability assessment was conducted in July 2013 using an environmental and socio-economical stand point. Identification of the vulnerability issues were grouped into indicators (climate, island morphological, marine resources and socio-economical changes), with each given a scale of 1-5.and attributes in the form of a semi-structured questioner. To check for the type and severity of a disaster, 62 respondents were asked to rank the disaster on a scale of 1-4. Results indicate that the majority of respondents find that change in climate, island morphology, marine resources and socio-economical conditions hardly affect them. The disaster that they fear the most is the danger of losing their source of income. In terms of vulnerability index, Bone Tambu and Lumu-Lumu islands are under very high vulnerability for Island and Socio-economic change. In terms of Climate and Marine Resource change, there are no significant differences among the islands. The trends show that these two categories fall under medium to high, with marine resource dynamic change always being higher than the climate change index, except in Kapoposang Island. Overall, there are no differences between each zonation in vulnerability indexes.